Desarrollo sostenible y turismo en el centro poblado de San Joaquín de Omaguas Iquitos 2022 - Mego del Aguila, Nelida Patricia (2024)
The objective of the research was to determine the relationship between sustainable development and tourism in the San Joaquín de Omaguas Populated Center, Iquitos 2022, where an applied type study, correlational level and non-experimental design was chosen, made up of a population of 478 inhabitants taking the sample of 213 inhabitants, the same ones who were surveyed through a questionnaire for data collection. Concluding that sustainable development was rated as medium (26%) since the population rarely makes an effort to improve their commercial activity, as well as sometimes they frequently participate in the social activities of their community, since sometimes they have participated in environmental education programs; On the other hand, tourism is at a medium level (27%), this is due to the influx of people who visit the town center and its resources at least for one day; In addition, it is very difficult to see a large influx of tourists from the interior of the country. Finally, the relationship between sustainable development and tourism is positive and considerable, with a correlation coefficient of 0.752 and a significance of 0.000.